2012
DOI: 10.1021/es204649a
|View full text |Cite
|
Sign up to set email alerts
|

Fe Atom Exchange between Aqueous Fe2+ and Magnetite

Abstract: The reaction between magnetite and aqueous Fe(2+) has been extensively studied due to its role in contaminant reduction, trace-metal sequestration, and microbial respiration. Previous work has demonstrated that the reaction of Fe(2+) with magnetite (Fe(3)O(4)) results in the structural incorporation of Fe(2+) and an increase in the bulk Fe(2+) content of magnetite. It is unclear, however, whether significant Fe atom exchange occurs between magnetite and aqueous Fe(2+), as has been observed for other Fe oxides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 79 publications
11
142
0
1
Order By: Relevance
“…As proposed in the literature, we can assume that the ferrous ions, bound on the surface of iron oxide, could activate molecular oxygen via a single-electron reduction pathway producing ROS that are capable of reducing the pollutants [8,22]. Our results on singlet oxygen formation support this assumption.…”
Section: Catalytic and Photocatalytic Activitysupporting
confidence: 87%
“…As proposed in the literature, we can assume that the ferrous ions, bound on the surface of iron oxide, could activate molecular oxygen via a single-electron reduction pathway producing ROS that are capable of reducing the pollutants [8,22]. Our results on singlet oxygen formation support this assumption.…”
Section: Catalytic and Photocatalytic Activitysupporting
confidence: 87%
“…Conduction of electrons through this matrix would allow TIE-1 (and potentially other FeOBs) access to electrons from remote electron donors, including Fe(II) (Supplementary Fig. 7), via processes such as electron conduction and iron atom exchange [30][31][32] . Indeed, recent studies have shown that conductive minerals can facilitate electron transfer to microbes from remote electron donors (including other microbes) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption of Ca 2+ , Ni 2+ and Fe 2+ to the magnetite surface progressively increases across this pH range (Vikesland and Valetine, 2002),. In the case of Fe 2+ , previous work on iron (oxyhydr)oxides including magnetite (Yanina and Rosso, 2008;Handler et al, 2009;Gorski et al, 2012) suggests that provided Fe 2+ can interact with the mineral surface, charge transfer can occur to the mineral lattice (see Figure 5b). We therefore infer that the influence of Fe 2+ adsorption on the phase response is likely to arise from redox reactions or charge transfer between adsorbed Fe 2+ and magnetite (such as reactions (1) and (2) described previously); the strong sensitivity of the phase peak frequency to increasing pH results from charge transfer via increasing amounts of adsorbed Fe 2+ ions.…”
Section: And) ('mentioning
confidence: 97%
“…It is an n and p type small band gap semiconductor at room temperature with the highest electrical conductivity of any oxide, of 1 -10 1 m 1 (Cornell and Schwertmann, 2003). Mobile charges within the magnetite lattice may be either electron or hole polarons situated on lattice sites occupied by Fe atoms, which migrate by electron hopping (Tsuda et al, 2000;Skomurski et al, 2010), or mobile Fe 2+ ions hopping between unoccupied lattice sites (Gorski et al, 2012). The rapid movement of such charges within the magnetite lattice gives rise to its high electrical conductivity (Skomurski et al, 2010;Gorski et al, 2012).…”
Section: '% ( )And% ('mentioning
confidence: 99%
See 1 more Smart Citation